Light‐induced degradation and regeneration of multicrystalline silicon Al‐BSF and PERC solar cells. Issue 12 (16th November 2016) - Padmanabhan, Mrinalini; Jhaveri, Krutarth; Sharma, Romika; Basu, Prabir Kanti; Raj, Samuel; Wong, Johnson; Li, Joel
Abstract : Light‐induced degradation (LID) is a well‐known problem faced by p‐type Czochralski (Cz) monocrystalline silicon (mono‐Si) wafer solar cells. In mono‐Si material, the physical mechanism has been traced to the formation of recombination active boron‐oxygen (B–O) complexes, which can be permanently deactivated through a regeneration process. In recent years, LID has also been identified to be a significant problem for multicrystalline silicon (multi‐Si) wafer solar cells, but the exact physical mechanism is still unknown. In this work, we study the effect of LID in two different solar cell structures, aluminium back‐surface‐field (Al‐BSF) and aluminium local back‐surface‐field (Al‐LBSF or PERC (passivated emitter and rear cell)) multi‐Si solar cells. The large‐area (156 mm × 156 mm) multi‐Si solar cells are light soaked under constant 1‐sun illumination at elevated temperatures of 90 °C. Our study shows that, in general, PERC multi‐Si solar cells degrade faster and to a greater extent than Al‐BSF multi‐Si solar cells. The total degradation and regeneration can occur within ∼320 hours for PERC cells and within ∼200 hours for Al‐BSF cells, which is much faster than the timescales previously reported for PERC cells. An important finding of this work is that Al‐BSF solar cells can also achieve almost complete regeneration, which has not been reported before. The maximum degradation in Al‐BSF cells is shown to reduce from 2% (relative) to an average of 1.5% (relative) with heavier phosphorus diffusion. Abstract : In recent years, light‐induced degradation (LID) has been identified to be a significant problem for multicrystalline silicon (multi‐Si) passivated emitter and rear cell (PERC) solar cells. LID and regeneration has been observed for multi‐Si PERC cells but not for aluminium back surface field (Al‐BSF) cells. The authors report for the first time that multi‐Si Al‐BSF solar cells can also achieve almost complete regeneration after LID under 1 sun and elevated temperature.